Lara Elizabeth Putnam. The Company They Kept. Migrants and the Politics of Gender in Caribbean Costa Rica, 1870-1960. The University of North Carolina Press, 2002 - Alvarenga Venutolo, Patricia (Revista de historia., 2002)
This book explores the cultural dynamics of the Costa Rican Caribbean through the historical processes of gender construction and ethnicity. Although in our academic practice we often refer to the historical character of these categories, in historical production it is difficult to find studies that analyze their dynamism with the depth that Putnam does. Through an imaginative use of quantitative and qualitative sources, the author portrays the cultural construction of the Caribbean and carefully integrates the socio-economic framework in which it takes place. The migratory trends and the economic conjunctures, analyzed in detail, allow the author to construct the scenarios of the cultural world.